Elaborasi Penggunaan Istilah Covid-19 Terhadap Pemahaman Masyarakat - Sri - Widiastutik (Universitas Bina Sarana Informatika, 2021)
The COVID-19 pandemic that is threatening the world has caused anxiety for all parties, including the people in Denpasar City. Various attempts have been made to make the situation stable, one way is to share information within a positive elaboration terminology. The information is certainly delivered by foreign words that are currently so prevalent, and appears in one click through the Google search engine. In order to convey the intent and meaning that can be properly channeled to all levels of society, Policies related to handling the COVID-19 pandemic through the elaboration of several foreign terms such as lockdown, swab test, social distancing, etc. are required. This study aimed to find out how the foreign words can be well accepted by the community without risking the existence of Indonesian language. As a descriptive qualitative method, the main data is Covid terms that are informed to the public in Denpasar are collected using a polling technique through randomly distributing questionnaires and simulation. Finding data was used survey & observation methods, as well as documentation. It is hoped public can understand and implement the appeal as expected by the government, without reducing the existence of good and correct Indonesian.Keywords: elaboration, foreign words, covid term